POLA KOMUNIKASI INTERPERSONAL SECARA LISAN DAN TULISAN KEPALA SEKOLAH DAN GURU DI SDN 06 JOMBANG KOTA TANGERANG SELATAN - AHMAD ZAINAL ARIFIN; ABDURROCHMAN; SUPATMI (UNISAN JURNAL, 2024)
This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews and participatory observation with the Principal and Teachers at SDN 06 Jombang Kota Tangerang Selatanlu. The results of the study show that verbal and written interpersonal communication patterns between the principal and teachers at SDN 06 Jombang Kota Tangerang Selatanlu tend to be formal and planned based on orders or instructions. The Principal is in control of both oral and written communication, while the teacher tends to be the recipient of information and responds to the Principal's requests or Directions. Apart from that, there is also more open and collaborative interpersonal communication when the Principal and the Teacher develop common ideas for the benefit of the school. In conclusion, the pattern of interpersonal communication between the principal and teachers at SDN 06 Jombang Kota Tangerang Selatanlu tends to be formal and modified in terms of orders or instructions, but there are also patterns of interpersonal communication that are more relaxed and open when in informal situations or when building ideas together. The advice given is the need to improve open and collaborative interpersonal communication between school principals and teachers to increase effectiveness and efficiency in achieving school goals. Keywords : Teacher, Interpersonal Communication, Principal